Effects of hypotension induced with sodium nitroprusside on the cerebral circulation before, and one week after, the subarachnoid injection of blood. Issue 1 (January 1988) - Fitch, W; Pickard, J D; Tamura, A; Graham, D I
Abstract : Cerebral blood flow (CBF) and mean arterial pressure (MAP) were monitored in six normal baboons and six further animals in which an artificial subarachnoid haemorrhage (SAH) had been induced one week previously. MAP was reduced by the infusion of sodium nitroprusside. In the normal animals with administration of sodium nitroprusside, CBF increased initially but started to decrease as MAP was reduced below 65 mm Hg and fell below its baseline value when MAP was less than 50 mm Hg. In the SAH group, there was no initial hyperaemic response and CBF fell below baseline values when MAP was reduced below 50 mm Hg. When, during the infusion of the sodium nitroprusside, MAP was returned to normal using angiotensin, CBF increased above its baseline value. These results suggest that the cerebrovascular effects of sodium nitroprusside are the net result of competition between direct cerebral vasodilatation, falling arterial blood pressure and the degree of impairment of the "autoregulatory" mechanism. Evidence of ischaemic brain damage was found in the arterial boundary zones of both groups of animals.